2002
DOI: 10.1037/1089-2699.6.3.219
|View full text |Cite
|
Sign up to set email alerts
|

Predicting attendance and expectations for group therapy.

Abstract: Inconsistent membership is one of the leading problems in groups. Group therapy participants (N ϭ 310) from 2 university counseling centers were studied over a period of 7 years to examine interpersonal style, expectations, and attendance in group therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 29 publications
2
61
1
2
Order By: Relevance
“…Such positive expectancy is often described as the primary factor to impart to clients during the initial phase of therapy. Positive expectations for group therapy and hope for personal change have continued to emerge in the literature as crucial to the process and outcome of group treatments (Cox et al, 2004;Leary & Miller, 1986;MacNair-Semands, 2002;Piper & McCallum, 1994;Yalom, 2005). Mackenzie (1987), in line with the findings of kivlighan and Goldfine (1991) and Reddon and colleagues (1999), found that hope is a significant variable for group members, particularly in the first stages of a group.…”
Section: Factor Structurementioning
confidence: 96%
“…Such positive expectancy is often described as the primary factor to impart to clients during the initial phase of therapy. Positive expectations for group therapy and hope for personal change have continued to emerge in the literature as crucial to the process and outcome of group treatments (Cox et al, 2004;Leary & Miller, 1986;MacNair-Semands, 2002;Piper & McCallum, 1994;Yalom, 2005). Mackenzie (1987), in line with the findings of kivlighan and Goldfine (1991) and Reddon and colleagues (1999), found that hope is a significant variable for group members, particularly in the first stages of a group.…”
Section: Factor Structurementioning
confidence: 96%
“…For example, MacNair-Semands (2002) examined session attendance for 310 group therapy participants. She found that angry, hostile, and socially inhibited group members had poorer attendance.…”
Section: Predicting Group Attendance Using In-session Behaviorsmentioning
confidence: 99%
“…In a survey of 96 clinical and 110 non-clinical subjects, Slocum (1987) found unfavourable expectations of group work, such as concerns that it was unpredictable, not as effective as individual therapy and that it could be detrimental. MacNair-Semands (2002) found that clients with previous therapy experience reported more positive expectations of group work but fewer positive expectations were found with clients reporting greater substance misuse and more somatic symptoms. These negative attitudes towards group work and the risk of drop out emphasise the need to assess and prepare clients for group work and to give them an informed choice.…”
Section: Introductionmentioning
confidence: 87%
“…An important factor reducing the effectiveness and cost effectiveness of group therapy is inconsistent attendance and drop out (MacNair-Semands, 2002;Budman et al, 1988). Drop out during group therapy is also likely to reduce the effectiveness of the therapy for the group as a whole.…”
Section: Introductionmentioning
confidence: 99%